(untitled) (European Bison Conservation Newsletter, 2015)
First attempts to start European bison breeding in Upper Silesia were made in 1865 by the prince of Pszczyna. Jan Henryk XI Hochberg exchanged with the tsar Alexander IInd 20 red deer from Pszczyna forest for four European bison from Białowieża. This initiated 150 years history of European bison breeding at this estate. At first, the animals were kept in small enclosure in the Murcki Forestry Inspectorate. In following years, the herd was moved to extensive area of Pszczyna forests, to 11,000 hectares enclosure. After the World War II, a new enclosure was built in Międzyrzecze Forestry over the area of 600 ha (now 742 ha), where the European bison have been bred ever since. Two individuals born at Pszczyna: Planta and Plebejer were very important for species restitution and their offspring significantly contributed to the gene pool of contemporary European bison.